Simulation of sediment accumulation for the river watershed using SWAT software: A case study on Ahar Chai river watershed in northwest of Iran - Anis Shafinezhad; Yousef Hasanzadeh; Sayed Saeed Rasinezami (Journal of Applied Research in Water and Wastewater, 2025)
This paper presents the results of a study that simulates the sediment routing of the Ahar Chai river using the hydrologic model which calculates the accuracy of using the soil and water assessment tool (SWAT) to simulate the runoff and sediment in watershed areas that could help to predict the amount of sediment in the future. Therefore, in this paper, sediment production in the upper Ahar Chai watershed, located in East Azarbaijan province - Ahar city, was simulated by using the hydrological model of SWAT, which is an addition to the Arc-GIS environment. The model's effectiveness in this area's hydrological simulation was assessed. sequential uncertainty fitting-2 (sufi-2), a SWAT-CUP sub-module computer program was applied to optimize the parameters of SWAT using monthly observed runoff and sediment data at the Ahar Chai watershed for calibration, validation, and uncertainty analysis. In the climatological studies, data from the Ahar synoptic station were used from 1994 to 2015. The Ahar Chai basin model was used from 1994 to 2015 for precipitation data. The monthly average discharge and sediment data were also used from the Orang hydrometric and sedimentation station in the period 2000-2015. The observed statistical data of flow and sediment measured for 22 years were selected for model simulation. The determination coefficient (R2) and the Nash-Sutcliffe coefficient (NS) in the calibration stage for sedimentation were 0.81 and 0.66 respectively, and also in the validation stage, were 0.74 and 0.71. The results highlight the model’s potential for simulating sediment yield and streamflow under varying climatic and land use conditions, with performance metrics comparable to those found in similar global studies. However, this study also provides unique insights into the regional-specific challenges of applying SWAT in regions with high variability in precipitation, land use, and topography. Notably, the influence of vegetation covers on sediment yield, as well as the importance of high-quality, region-specific data for model calibration, are key findings. This research contributes to the broader body of knowledge by offering an in-depth analysis of SWAT’s performance in the Ahar Chai basin, while also addressing the gaps in current modeling efforts related to sediment transport in mountainous, semi-arid environments. The findings pave the way for future advancements in hydrological modeling and watershed management in similar regions, particularly through the integration of more detailed data and enhanced uncertainty analysis methods.